Different Forms of Civil Activity and Employment in Hungary and Abroad, and the Development of Student Drop-out - Markos, Valéria; Kocsis, Zsófia; Dusa, Ágnes Réka (Central European Journal of Educational Research, 2019)
Young people involved in higher education have created a specific culture, to which, in addition to their studies, social and cultural activities associated with university life are also related (Kozma, 2006). Among these activities, student employment and participation in civic organizations should be highlighted. Voluntary and paid work among higher education students is increasing. These activities have several advantages in terms of future benefits; however, the attracting role of the labour market is one possible reason for dropout. In our current research, we emphasize the role of employment and civil activity in the development of student dropout. Masevičiūtė et al. (2018) found that a quarter of students stopped studying for work-related reasons. In addition, a negative perception of the marketability of the course they are on may lead to the interruption of university studies. In our study, we analysed the extent to which students are willing to interrupt their higher education studies in exchange for voluntary work. In our current research, we examined how often and for what reasons students who dropped out did paid work and volunteering during their studies.